2017
DOI: 10.3892/ol.2017.6535
|View full text |Cite
|
Sign up to set email alerts
|

Silencing DNA methyltransferase 1 leads to the activation of the esophageal suppressor gene p16 in vitro and in vivo

Abstract: Abstract. Previous studies have demonstrated that DNA methyltransferase 1 (DNMT1) is required for the maintenance of DNA methylation and epigenetic changes that may lead to the development of esophageal squamous cell carcinoma (ESCC). In order to investigate whether the silencing of DNMT1 protects tumor suppressor genes, including p16, and is able to be used as a potential therapy for human ESCC, short hairpin RNA targeting DNMT1 (shRNA-DNMT1) was synthesized and transfected into the human ESCC lines KYSE150 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…p16INK4a inhibits cyclin‐dependent kinases (CDK) CDK4 and CDK6, and thereby preventing G1‐to‐S cell‐cycle phase progression; thus, the methylation of p16INK4a is reported cell‐cycle progression 31 . As well as, the inhibition of DNMT1 leads to the activation of p16, RUNX3, SFRP1, and E‐cadherin 29,32–34 . It shows that DNMT could influence the proliferation by leading methylation of suppressor genes that act directly or indirectly in cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…p16INK4a inhibits cyclin‐dependent kinases (CDK) CDK4 and CDK6, and thereby preventing G1‐to‐S cell‐cycle phase progression; thus, the methylation of p16INK4a is reported cell‐cycle progression 31 . As well as, the inhibition of DNMT1 leads to the activation of p16, RUNX3, SFRP1, and E‐cadherin 29,32–34 . It shows that DNMT could influence the proliferation by leading methylation of suppressor genes that act directly or indirectly in cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that DNMT1 is required for the deactivation of p16 by DNMT1-mediated methylation that may lead to the development of ESCC [ 18 ]. Growing evidence shows that overexpressed HDACs are associated with tumorigenesis in ESCC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the activation of PAR4 was able to increase p16 expression and decrease DNMT1 and HDAC2 expression in ESCC cells. Therefore, it seems more likely that the effect of PAR4 on DNMT1 and HDAC2 expression results in promoting p16 gene transcription [ 18 , 31 ]. These results suggested that PAR4 was able to upregulate p16 levels through inhibition of DNMT1 and HDAC2 expression in ESCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations